Analisis Spasial Sebaran Ruang Terbuka Hijau Publik (RTHP) Menggunakan NDVI dan Getis Ord G* di Kota Yogyakarta - sista, Satwika; Kurniawan, Andri; Muta'ali, Luthfi (Geography Education Study Program, Universitas Kanjuruhan Malang, 2025)
Public Green Open Space (RTHP) has an important role in maintaining environmental quality and urban sustainability, both in terms of ecology, social, and aesthetics. However, the distribution and quality of RTHP is often uneven in urban areas, including in Yogyakarta City. This study aims to analyse the quality of vegetation and spatial distribution of RTHP using the Normalised Difference Vegetation Index (NDVI) approach and Getis Ord G* spatial analysis. NDVI is calculated using Sentinel-2A satellite imagery and then averaged to determine the value in each RTHP to determine the level of vegetation in it. Meanwhile, the Getis Ord G* method was used to identify spatial clusters of green spaces per administrative area. The results showed that most of the green spaces had low to moderate levels of vegetation. The spatial distribution of RTHP in Yogyakarta City shows clusters of RTHP hotspots in Umbulharjo and Kotagede sub-districts, and coldspots in Gondomanan and Ngampilan sub-districts. These results indicate